Combined Scattering of Radiation Belt Electrons Caused by Landau and Bounce Resonant Interactions With Magnetosonic Waves. Issue 17 (24th September 2019) - Fu, Song; Ni, Binbin; Zhou, Ruoxian; Cao, Xing; Gu, Xudong
Abstract: We develop a full relativistic test particle code to model the combined electron scattering effect of Landau and bounce resonances with magnetosonic waves. Test particle simulations of magnetosonic wave‐electron interactions indicate that the two resonances coexist to affect radiation belt electrons at different energies and pitch angles, and the resultant combined pitch angle scattering and energy diffusion can reach the rates of ~10 −4 and ~10 ‐5 s, respectively, for electrons ~40–500 keV at pitch angles ~   70 ° –   80° for the given wave model (~200 pT) inside the plasmapause at L = 4.5. Comparisons with the quasi‐linear theory results show that the test particle combined scattering rates are generally an order of magnitude weaker, possibly because the electrons are moved out of the Landau resonance by the advective effect of the bounce resonance. Our investigation demonstrates that the Landau and bounce resonances with magnetosonic waves cannot be treated independently or additively in terms of quasi‐linear theory to simulate the associated radiation belt electron dynamics. Plain Language Summary: The radiation belt electrons are believed to resonate with magnetosonic (MS) waves in ways of Landau resonance and bounce resonance. In previous studies, the MS wave‐particle interactions were separately evaluated through numerical calculations, that is, the formulism of quasi‐linear theory for Landau resonance and bounce resonance. However, each time the quasi‐linear theory calculations can involve only one resonance mechanism and lack the exploration upon the net scattering effect caused by MS waves. Here we use the test particle simulations to examine the wave‐particle interactions including both the Landau and bounce resonances with MS waves, and quantify the resultant radiation belt electron scattering coefficients for quantitative comparisons with the quasi‐linear theory results. Key Points: Landau and bounce resonances induced by MS waves can coexist to scatter radiation belt electrons Test particle computations of combined pitch angle scattering and energy diffusion coefficients are generally weaker than those obtained from the quasi‐linear theory MS wave‐driven electron scattering can be dominated by the bounce resonance